2006
DOI: 10.1128/jb.188.4.1245-1250.2006
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Represses the Synthesis of the Nickel Permease NixA ofHelicobacter pylori

Abstract: Nickel acquisition is necessary for urease activity, a major virulence factor of the human gastric pathogen Helicobacter pylori. NixA was identified as a specific nickel uptake system in this organism. Addition of small amounts of nickel to media strongly stimulates urea hydrolysis. On the other hand, high nickel concentrations are deleterious to cell growth. As a possible protective reaction, nickel uptake seems to be reduced in H. pylori grown in nickel-rich media. These observations led to investigations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
58
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 55 publications
4
58
1
Order By: Relevance
“…Deletion of nikR in each mutant background restored 63 Ni accumulation to levels similar to those of a nikR mutant strain (ϳ120 to 150% of the level in the parental strain). These data provide further evidence that NikR activity is increased in the urease pathway mutants and indicate that the decrease in nixA and frpB4 levels results in decreased NixA and FrpB4 protein levels during this assay, consistent with a previous report of the rate of NixA turnover under similar conditions (44).…”
supporting
confidence: 79%
See 2 more Smart Citations
“…Deletion of nikR in each mutant background restored 63 Ni accumulation to levels similar to those of a nikR mutant strain (ϳ120 to 150% of the level in the parental strain). These data provide further evidence that NikR activity is increased in the urease pathway mutants and indicate that the decrease in nixA and frpB4 levels results in decreased NixA and FrpB4 protein levels during this assay, consistent with a previous report of the rate of NixA turnover under similar conditions (44).…”
supporting
confidence: 79%
“…1a to d), respectively, in a NikR-dependent manner (14,17,18,44). nixA and frpB4 levels in the nikR mutant strain treated with DMG or NiCl 2 were also increased relative to levels in the parent strain ( Fig.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…For instance, while we have shown that the Hpn and Hpn-like proteins play a role in nickel (and other metal) detoxification, the role of these proteins in concert with other metal toxicity prevention mechanisms is not understood. High nickel levels repress expression of the NixA transporter and the other Niresponsive outer membrane protein studied (7,9,39), presumably to aid in preventing nickel toxicity; perhaps the His-rich proteins provide a more rapid (detoxification) response to transient nickel fluctuations before the (transporter) expression changes can have an affect. Also, Ni efflux pumps (CznABC) that are proposed to pump out excess nickel have been identified (28); this adds another feature to the overall Ni homeostasis/detoxification picture.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the nik-specific repressor NikR allows expression of the nik operon only at low environmental nickel levels (de Pina et al, 1995). In H. pylori, NikR is crucial to controlling both nickel transport (Ernst et al, 2005;Wolfram et al, 2006) and urease expression (van Vliet et al, 2002). The H. pylori NikR is a highly pleiotropic regulator that is able to act as a repressor or activator (Ernst et al, 2005) of a large number of genes (Contreras et al, 2003), as well as responding to low pH (Bury-Moné et al, 2004;van Vliet et al, 2004).…”
Section: Discussionmentioning
confidence: 99%